Características socioeconômicas e ambientais da produção de mel apícola no Estado de Roraima - Cruz, Valeska Regina Rodrigues da (2021)
Of the products originating from beekeeping, honey is the best known for its therapeutic and nutritional use. The lack of current information on this activity and knowledge of illegal honey sales boosted the planning of this work, which aimed to analyze the activities of the beekeeping sector in Roraima, with emphasis on honey production, from a socioeconomic and environmental perspective. The techniques used were the application of forms with closed questions, voice recorder and field diary, used during the semi-structured interview with beekeepers and during visits to their apiaries. To complement the research, data were collected from the digital platforms IBGE and DATASUS, which have statistics on beekeeping production and records on public health. The data obtained in this research provided knowledge about the current situation of beekeeping in Roraima, identified problems that influence both the commercialization of beekeeping honey, as well as the recognition of the productivity of Roraima honeys, as well as an understanding of the perception of beekeepers about the importance of their activity for the environment and the vulnerability of these professionals to the defensiveness of Africanized bees.